Stability Results Of New Rice Pulses (Oryza sativa L.) F4 and F5 - Sy, Yogi Pratama; Kartahadimaja, Jaenudin; Syuriani, Eka Erlinda (Politeknik Negeri Lampung., 2018)
The challenge for plant breeders can not be separated from the interaction effects between genotypes and the environment, where the tested strains show different results at each test site. Therefore, to know a strain or genotype that has a level of stability it is necessary to do the testing phase. The currently developed strains are RG1, RG2, RG3, and RG4. Currently the strains have entered the third generation. Furthermore, the four rice strains will be planted in the fourth generation and continued by the fifth generation. This research was conducted at Field Polytechnic of Lampung State of Lampung, Bandar Lampung on September 2015 - January 2016 planting F4 and January - May 2016 planting F5. The objective of this research is to obtain new strain of rice that is able to maintain the stability of the results by looking at the phenotypic appearance character and the potential yield that is planted on F4 and F5. The design used in this study is the design of split plot with main plot treatment using two generations (F) that is F4 and F5. While in sub plots using 4 new rice strains (G) are RG1, RG2, RG3, and RG4. Data were analyzed by LSD Test at 5% level. Stability analysis using Francis and Kenneberg (1978) models, by looking at the mean squares (Si2) and the Coefficient of Varians (CVi). From the result of observation of stability result of four rice strains in two different planting generations it can be concluded that the strains that exhibit phenotypic character and stable yield potential on F4 and F5 are RG1 and RG2. The strings showing potential unstable results on F4 and F5 are RG3 and RG4.